Potentiality of Formulated Pseudomonas Fluorescens and Bacillus Subtilis for the Management of Sheath Blight Disease of Rice Under Field Condition (Journal of the Bangladesh Agricultural University, 2024)
Rice production is severely affected by sheath blight disease in Bangladesh which is caused by a fungus Rhizoctonia solani that is still merely managed by synthetic chemical fungicides. In this study, different isolates of Pseudomonas fluorescens and Bacillus subtilis were evaluated to assess their inhibitory effects against R. solani both in- vitro and field condition following dual culture method in order to formulate technique for the management of sheath blight of rice. Among all the isolates, P. fluorescens (Pf- 7 and Pf- 8) and B. subtilis (Bs-17 and Bs-21) showed the highest in –vitro mycelial growth suppression of the pathogen. Based on the in-vitro mycelial growth suppression performance, fourteen treatments combinations, either single or in consortia of antagonistic bacteria in talc-based formulations were applied by root dipping. All the formulated bacterial isolates showed significant reduction in disease and severity compared to untreated control and chemical fungicide. At 90 DAT, both the disease incidence and severity were found lowest in T11 (31.67 % and 37.33 % respectively) where the seedlings were treated for 24 hours with consortium of Pf-7 + Pf- 8 formulated in talc followed by in T12 (32.00 % and 38.00 %) where the seedlings were treated for 24 hours with consortium of Bs-17 + Bs-21 formulated in talc respectively. Vegetative and yield parameters were also significantly increased in both T11 and T12. The highest yield as well as Benefit Cost Ratio (BCR) were found in T11 (2.50 kg/ m2 and 2.20) followed by T12 (2.49 kg/m2 and 2.18). Thus, the consortia of bacterial isolates (Pseudomonas fluorescens and Bacillus subtilis) with seedling dipping time for 24 hour represents a promising alternative to chemical fungicides for the management of sheath blight of rice in field condition.J Bangladesh Agril Univ 22(3): 342-351, 2024